GEOMETRIC UNCERTAINTY ANALYSIS OF A CENTRIFUGAL COMPRESSOR USING KRIGING MODEL. Issue 5 (January 2021) - Li, Shujiang; Huang, Min; Liu, Xuejun
Abstract: Centrifugal compressor, which is an important turbomachinery, plays a significant role in the gas turbine engine. Various uncertain factors in the manufacturing process can lead to the geometric variations, which often cause noticeable variations in compressor performance. In this paper, a surrogate-based uncertainty analysis method is used to investigate the effect of geometric uncertainty on the aerodynamic performance of a centrifugal compressor. Firstly, a scaled-up version of NASA DDA's 404-III centrifugal compressor is chosen as the research object. Considering the structural features of the compressor, a parameterized model with 38 independent control parameters is established to define the geometry of the compressor, enabling rapid modification of the geometry. Then, a widely-used simulation method based on computational fluid dynamics is employed to predict the aerodynamic performance at a series of specified geometries generated using Latin Hypercube Design. Next, based on the sample data, two Kriging models are built to emulating the complex functional relationship between the control parameters and the performance of compressor. Finally, a Kriging model-based Monte Carlo simulation method is used to perform the geometric uncertainty analysis. After specifying a reasonable probability distribution for each control parameter, the statistical distributions of the compressor performance are obtained and analyzed. The analysis results yield new insights for compressor designers.